Music for the Cochlear Implant: Audience Response to Six Commissioned Compositions - Au, Agnes; Marozeau, Jeremy; Innes-Brown, Hamish; Schubert, Emery, A/Prof.; Stevens, Catherine J., Prof. (Seminars in Hearing, 2012)
Although cochlear implant (CI) users enjoy good speech understanding, music perception is still difficult or unpleasant for many. This study aimed to assess cognitive, engagement, and auditory responses to new music composed specifically for CI users. From 407 concertgoers who completed a questionnaire, responses from groups of normally hearing listeners (n = 44) and CI users (n = 44), matched in age and musical ability, were compared to determine whether specially commissioned works would elicit similar responses from both groups. No significant group differences were found on measures of interest, enjoyment, and musicality, whereas ratings of understanding and instrument localization and recognition were significantly lower for CI users. Overall, ratings of the music were typically higher for percussion pieces. The concert successfully elicited similar responses from both groups in terms of interest, enjoyment, and musicality, although technical aspects, such as understanding, localization, and instrument identification, continue to be problematic for CI users.
Keywords: Hearing loss; cochlear implant; music appreciation